Factors associated with overall quality of life among elderly enrolled in Basic Health Units - Espinosa, Mariano Martínez; Rodrigues, Dayane de Carvalho; Oliveira, Nathany Luzia de; Alves, Bryan Mariano Martínez; Marcon, Samira Reschetti (Ciência e Natura, 2022)
The aim this study was to evaluate the demographic, socioeconomic and health condition variables and the WHOQOL-BREF and WHOQOL-OLD domains associated to the overall quality of life registered in Basic Health Units. This is a cross-sectional study, with the population of elderly participants from eight Basic Health Units in the Municipality of Cuiabá-MT, considering a random sample of 317 elderly. For the data collection, a structured questionnaire was applied with demographic, socioeconomic and health questions, in addition to the WHOQOL-BREF and WHOQOL-OLD instruments. To associate the global quality of life with the variables and domains of the two instruments, the crude prevalence ratio and the robust Poisson multiple regression model were used. The variables and domains that showed the highest associations with overall quality of life were: health problems, health services used and the scores of the physical, environment and intimacy domains. The study results show that the indicated factors and domains constitute risk factors for the global quality of life of the studied elderly.